Prospects of manufacture of modern packaging materials with the application of bioddelessed polymer compositions - Litvyak, Vladimir V. (Journal of the Belarusian State University. Ecology, 2019)
The world market and application of biodegradable polymeric materials, and also their prospects in Belarus is shown. The basic biodecomposed polymeric materials, including received with use oxobiodegradables additives are characterised. It is found, that the intensification of researches in the field of creation of biodegradable polymers is one of perspective directions of the decision of the global environmental problem related to environmental contamination by a waste of polymeric materials.